Promoting respectful maternity care in rural Tanzania: nurses' experiences of the "Health Workers for Change" program - Gail Webber; Bwire Chirangi; Nyamusi Magatti (BMC, 2018)
Abstract Background Disrespectful and abusive care of women during their pregnancies has been shown to be a barrier for women accessing health care services for antenatal care and delivery. As part of an implementation research study to improve women's access to health care services in Rorya District, Mara, Tanzania, we conducted a pilot study training reproductive health care nurses to be more sensitive to women's needs based on the "Health Workers for Change" curriculum. Methods Six series of workshops were held with a total of 60 reproductive health care nurses working at the hospitals, health centres and dispensaries in the district. The participants provided comments on a survey and participated in focus groups at the conclusion of the workshop series. These qualitative data were analyzed for common themes. Results The participants appreciated the training and reflected on the poor quality of health care services they were providing, recognizing their attitudes towards their women patients were problematic. They emphasized the need for future training to include more staff and to sustain positive changes. Finally, they made several suggestions for improving women's experiences in the future. Conclusions The qualitative findings demonstrate the success of the workshops in assisting the health care providers to become aware of their negative attitudes towards women. Future research should examine the impact of the workshops both on sustaining attitudinal changes of the providers and on the experiences of pregnant women receiving health care services.